Sarcopenia in interstitial lung disease - Robert Sheehy; Samuel McCormack; Caitlin Fermoyle; Tamera Corte (European Respiratory Review)
Background Interstitial lung disease (ILD) encompasses a heterogeneous group of chronic lung conditions with considerable variability in prognosis and response to treatment. People with reduced muscle mass and function, known as sarcopenia, have a higher risk of mortality and adverse clinical outcomes both in the general population and in other chronic disease states. The importance of sarcopenia across the spectrum of patients with ILD is not well established. Objectives In this narrative review, we explore the prevalence and clinical implications of sarcopenia in patients with ILD, evaluate the optimal methods to diagnose sarcopenia in this patient population and review treatment interventions. Findings Almost one third of patients with chronic forms of ILD have evidence of sarcopenia. Sarcopenia is associated with adverse clinical outcomes and increased risk of mortality in select populations with ILD. Screening tests such as the SARC-F (strength, assistance walking, rise from a chair, climb stairs, falls) questionnaire and clinical assessment tools (including grip strength dynamometry) are well validated. Medical imaging modalities, including computed tomography, are hampered by lack of a gold standard and normative values, but have been used in patients with ILD in acute care and research settings. If sarcopenia is identified, multidimensional interventions such as pulmonary rehabilitation are beneficial. Conclusion Sarcopenia is common in patients with ILD and is associated with poorer outcomes. Accordingly, if identified, targeted interventions should be considered. Validated diagnostic criteria exist, but the optimal use of medical imaging techniques in this patient cohort remains an area of uncertainty.